Cool? Young people investigate living in cold housing and fuel poverty. A mixed methods action research study. (December 2017) - O'Sullivan, Kimberley C.; Howden-Chapman, Philippa; Sim, Dalice; Stanley, James; Rowan, Rebekah L.; Harris Clark, Isobel K.; Morrison, Lydia L.A.; ,
Abstract: Background: Living in cold housing conditions and risk of fuel poverty presents a range of physiological and psychosocial health risks. Limited research has specifically investigated the effects of fuel poverty on children and young people, and even less has been conducted with youth input into the research process. Methods: The Cool? Study used mixed methods, participatory action research carried out with youth researchers involved at all stages through questionnaire design, analysis, qualitative design, e-interviewing and dissemination of results. This article reports on results of an online survey of 656 adolescents aged 14–16 years completed at 17 schools in New Zealand. Sampling was based on selecting schools for invitation, with the probability of selection weighted proportional to school size, within strata defined by climate zone. Results from a small e-mail interview study of survey respondents who consented to follow-up are also reported. Results: The study found that almost half of the survey respondents (47%) felt their home was sometimes cold during the winter; a further 40% felt their home was often or always cold. More than two thirds of respondents (70%) had shivered inside at least once during winter. Respondents were more likely to report key indicators of fuel poverty depending on their self-reported ethnicity, with Māori at increased risk. Living in private rental housing or state-owned housing also increased risk of fuel poverty compared to those in owner-occupied dwellings. Participants of email interviews expressed concern about the widespread problem of cold housing for youth and a desire for Government intervention. Conclusion: The integrated results confirm that cold housing and risk of fuel poverty are important problems for young people in New Zealand. Results contribute to the evidence-base for policy targeting of schemes such as the Government-sponsored retrofitting of insulation to households with dependent children. Highlights: Mixed methods action research investigated cold housing among New Zealand youth. Participatory approach included youth throughout the research process. Online school-based survey found cold housing is a significant problem among youth. Risk of fuel poverty is higher among those in rental tenure and of Māori ethnicity. Young people support policy intervention to improve housing conditions for youth.